Are liana communities in linear canopy openings subject to edge effects? - Miranda, Beatriz Castro; Sansevero, Jerônimo Boelsums Barreto; Amorim, Thiago de Azevedo; Rodrigues, Pablo José Francisco Pena; Nascimento, Marcelo Trindade; Braga, João Marcelo Alvarenga (Plant ecology, 2022)
Studies have revealed a significant increase in liana abundance due to intense fragmentation and consequent edge effects in tropical forests. This study evaluated whether liana communities adjacent to linear canopy openings experience edge effects in the Brazilian Atlantic Forest. For vegetation sampling, 12 sampling units (20 × 50 m) were distributed among forest fragments with four sampling units in each of three treatments: old-growth forest, power line edge (40 years old and 100 m wide), and gas pipeline edge (20 years old and 25 m wide). All lianas with Diameter at Ground Height (DGH) ≥ 2.5 cm were measured. Subplots (20 × 20 m) were also allocated to measure individuals with DGH between 0.5 and 2.49 cm. Edge effects were determined using the parameters: abundance, basal area, species richness, and species composition. Edge and interior lianas were similar for all measured parameters for both diameters classes. There was a higher rate of infestation by lianas in larger trees both on the edges and interior. These linear openings resulted in only few alterations to liana community dynamics along edges, indicating that fragmentation from linear openings may result in a softer edge effect or that edge effects may even attenuate over time due to linear openings. Finally, liana infestation on larger trees suggests that tree structure plays an important role in structural patterns of liana communities.